Petalidium saxatile (Acanthaceae), a new species from Namibia - Swanepoel, Wessel; Dexter, Kyle G.; Adamo, Martino; Manzitto-Tripp, Erin A.; van Wyk, Abraham E. (Phytotaxa, 2025)
Petalidium saxatile, hitherto confused with P. canescens, and the widespread P. setosum, is here described as a new species. It is a range-restricted species, only known from the vicinity of Palmwag and southwards to the Bergsig area with an outlier population to the south of Khorixas in the Kaokoveld Centre of Endemism, northwestern Namibia. It grows mainly among basaltic rocks of the Etendeka Group on arid hillsides and along ephemeral riverbeds and drainage lines. Diagnostic characters for P. saxatile include the pale green appearance of the plants, vegetative parts with a dense white indumentum of relatively short dendritic trichomes appearing matted on young leaves, flowers borne in compact dichasia, and long simple eglandular trichomes on the bracts visible to the naked eye. The flowers of P. saxatile are distinctive in having the corolla lobes inside (adaxially) distinctly bicolorous: the upper and lateral lobes are pink or brown-pink, while the anterior lobe is yellow. Additionally, all lobes are discolorous in being much paler outside (abaxially). Furthermore, analyses of genetic data across many nuclear loci, generated using a ddRADseq approach, show the species to be genetically distinct from P. canescens. A comparison of key morphological features distinguishing P. saxatile from P. canescens and P. setosum, is provided. Based on IUCN Red List criteria, a provisional conservation assessment of Endangered (EN) is recommended for the new species. It is suggested that the Etendeka Tableland, to which P. saxatile is largely confined, may serve as a local subcentre of plant endemism within the larger Kaokoveld Centre of Endemism, at least for species in the genus Petalidium.